Safety and feasibility of thullium laser transurethral resection of prostate for the treatment of benign prostatic enlargement in overweight patients - Luca Carmignani; Maria Chiara Clementi; Claudia Signorini; Gloria Motta; Sebastiano Nazzani; Franco Palmisano; Elisa De Lorenzis; Michele Catellani; Alessandro Francesco Mistretta; Andrea Conti; Valeria Tringali; Maria Beatrice Costa; et al. (Asian Journal of Urology, 2019)
Objective: We aimed to determine safety and feasibility of thulium laser transurethral vapoenucleation of prostate (ThuVEP) for treatment of obese patients affected by benign prostatic hyperplasia (BPH). Methods: We retrospectively analysed data of 452 patients with BPH who underwent ThuVEP from February 2012 to March 2016 in a single center. Patients were divided into three groups according to body mass index (BMI, kg/m2): Normal weight (18.5 ≤ BMI < 25; Group A), overweight (25 ≤ BMI < 30; Group B) and obese (BMI ≥ 30; Group C), for a total of 412 patients evaluable for this study. Preoperative total serum prostate-specific antigen (PSA), digital rectal examination of the prostate, transrectal ultrasound (TRUS), renal ultrasound, urine culture, uroflowmetry, International Prostate Symptoms Score (IPSS), and Quality of Life (QoL) score were analyzed. Post-operative complications, hospital stay and days of catheterization, questionnaires and uroflowmetry at 1 and 3 months after surgery were evaluated. Preoperative data, surgical outcomes, complication rate and clinical outcomes were compared between groups. Results: The median age of patients was 69 years (Interquartile Range [IQR 10]). The preoperative median IPSS among groups was 19 (IQR 8.75), 20 (IQR 10), and 18 (IQR 10) respectively. At 1 and 3 months of follow-up, this value was 8 (IQR 7), 8 (IQR 4), 7 (IQR 5) and 5 (IQR 6.25), 5 (IQR 6), 6 (IQR 5), respectively (all p between groups > 0.05). There was no statistically significant difference among three groups as for hospital stay and days of catheterization (p > 0.05). Conclusion: Our results showed that ThuVEP was safe and feasible even in overweight patients with substantially enlarged prostate. Keywords: Laser, Thulium, Prostate, Overweight